2012
DOI: 10.1186/1472-6785-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in species interactions in simple aquatic bacterial communities

Abstract: BackgroundOrganisms modify their environment and in doing so change the quantity and possibly the quality of available resources. Due to the two-way relationship between organisms and their resource environment, and the complexity it brings to biological communities, measuring species interactions reliably in any biological system is a challenging task. As the resource environment changes, the intensity and even the sign of interactions may vary in time. We used Serratia marcescens and Novosphingobium capsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…According to our earlier study, a cross-feeding interaction is possible between S. marcescens and N. capsulatum . When the growth rate of each species was tested in a sterile-filtered medium where the other species had consumed the resources for 1 to 168 h, the growth rates in consumed medium were occasionally faster than in unconsumed medium [27]. Serratia marcescens had a relatively high growth rate in medium consumed by N. capsulatum for 1 to 10 h, whereas N. capsulatum had high growth rates in medium consumed by S. marcescens for 30 to 50 h [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to our earlier study, a cross-feeding interaction is possible between S. marcescens and N. capsulatum . When the growth rate of each species was tested in a sterile-filtered medium where the other species had consumed the resources for 1 to 168 h, the growth rates in consumed medium were occasionally faster than in unconsumed medium [27]. Serratia marcescens had a relatively high growth rate in medium consumed by N. capsulatum for 1 to 10 h, whereas N. capsulatum had high growth rates in medium consumed by S. marcescens for 30 to 50 h [27].…”
Section: Discussionmentioning
confidence: 99%
“…When the growth rate of each species was tested in a sterile-filtered medium where the other species had consumed the resources for 1 to 168 h, the growth rates in consumed medium were occasionally faster than in unconsumed medium [27]. Serratia marcescens had a relatively high growth rate in medium consumed by N. capsulatum for 1 to 10 h, whereas N. capsulatum had high growth rates in medium consumed by S. marcescens for 30 to 50 h [27]. However, results presented here show that when these species grew together for prolonged time, they did not evolve to be dependent on a cross-feeding interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Lawrence et al. ; Pekkonen and Laakso ). For example, three out of the four species in Lawrence et al.’s study were found to evolve adaptations for avoiding competition, when they evolved in polyculture (Lawrence et al.…”
Section: Discussionmentioning
confidence: 98%